The impact of single nucleotide polymorphisms on patterns of non-contact musculoskeletal soft tissue injuries in a football player population according to ethnicity - Pruna, Ricard; Ribas, Jordi; Montoro, Jose Bruno; Artells, Rosa (Medicina clinica, 2015)
The prevention, diagnosis, and management of non-contact musculoskeletal soft tissue injuries (NCMSTIs) related to participation in sports are key components of sport and exercise medicine. Epidemiological data have demonstrated the existence of interindividual differences in the severity of NCMSTIs, indicating that these injuries occur as a consequence of both extrinsic and intrinsic factors, including genetic variations. We have collected data on NCMSTIs suffered by 73 elite players of White, black African and Hispanic ethnicity of European football over the course of three consecutive seasons. We have also examined eight single nucleotide polymorphisms (SNPs) in genes related to tissue recovery and tissue repair in blood drawn from the players and correlated our findings with type and severity of injuries in each ethnic group. The frequency of the SNPs varied among the three ethnic sub-groups (p<0.0001). Among Whites, a significant relationship was observed between ligament injuries and ELN (p=0.001) and between tendinous injuries and ELN (p=0.05) and IGF2 (p=0.05). Among Hispanics, there was a significant relation between muscle injuries and ELN (p=0.032) and IGF2 (p=0.016). Interracial genotypic differences may be important in the study of NCMSTIs. A genetic profile based on SNPs may be useful tool to describe each individual's injuribility risk and provide specific treatment and preventive care for football players.